The enterprise value in assessing the cash flow discounting method - Аскарова, Ж. (Journal of Economic Research & Business Administration, 2017)
Estimates of the rights of the owners of the company, is the primary indicator of the company’s profit potential over time. The income approach is the basic principle is the principle of waiting. Method of discounting future revenues, as the present value of the future income from the acquisition of objects, successfully used for the assessment of real estate. The benefits of real estate transactions in the future, future revenues and revers yan time in the form of income during the period of ownership, ie the profit from the sale of the property at the end of the period of ownership. The enterprise value - the amount of income for several years and calculated as the difference between the amount of the borrowed funds are involved. Generates future income, expenses and cash flows. Future costs and the results of the evaluation of the company is to be determined within the reporting period and the amortization horizons. Computer horizons measured by the number of steps of the calculation. Discounted cash flow method, the assets of the enterprise value of their cash income is measured by the ability to import.